Director reorientation in a cell with time-dependent anchoring due to adsorption/desorption of LC molecules - Romanenko, A.; Pinkevich, I.; Reshetnyak, V.; Dozov, I.; Stoenescu, D. (Functional Materials, 2005)
Influence of adsorption/desorption process of nematic molecules at the nematic cell substrate on the nematic crystal director evolution in time that is due to external magnetic field has been considered. It is shown that boundary conditions at the cell surface evolve in accordance with the distribution of nematic molecular orientation in the cell bulk. During the time evolution, the orientation distribution function of molecules adsorbed at the cell substrate can exhibit two maxima. By switching off the magnetic field at the suitable moment, it is possible obtain a bistable nematic system. Рассмотрено влияние процесса адсорбции/десорбции молекул нематика на одной из поверхностей нематической ячейки на временную эволюцию директора нематического жидкого кристалла, обусловленную внешним магнитным полем. Показано, что граничные условия на поверхности ячейки согласуются с объемным распределением ориентации молекул нематика. В течение времени эволюции функция распределения ориентации молекул адсорбированных на поверхности ячейки, может иметь два максимума. Это позволяет получить бистабильную нематическую систему, если в соответствующий момент времени выключить магнитное поле. Розглянуто вплив процесу адсорбції/десорбції молекул нематика на одній із поверхонь нематичної комірки на часову еволюцію директора нематичного рідкого кристалу, зумовлену зовнішнім магнітним полем. Показано, що граничні умови на поверхні комірки узгоджуються з об’ємним розподілом орієнтації молекул нематика. Протягом часу еволюції функція розподілу орієнтації молекул адсорбованих на поверхні комірки може мати два максимуми. Це дозволяє отримати бістабільну нематичну систему, якщо у відповідний момент часу вимкнути магнітне поле.